Pharmacokinetics of nevirapine in HIV-infected children with and without malnutrition receiving divided adult fixed-dose combination tablets. - Pollock, L; Else, L; Poerksen, G; Molyneux, E; Moons, P; Walker, S; Fraser, W; Back, D; Khoo, S (2009)
OBJECTIVES: To determine the relationship between nutritional status and nevirapine exposure by comparing the pharmacokinetics of nevirapine in HIV-infected children of different ages with and without malnutrition receiving divided tablets of Triomune 30 (stavudine + lamivudine + nevirapine) in accordance with Malawi National Guidelines. METHODS: Children were recruited in weight-based dosage bands and nutritional status classified according to weight for height. Total and unbound plasma nevirapine concentrations were measured over a full dosing interval. Multivariate linear and logistic regression analyses were performed to determine the effects of malnutrition, age, dose and other factors on nevirapine exposure and likelihood of achieving therapeutic nevirapine trough concentrations. RESULTS: Forty-three children were recruited (37 included for analysis). Mild to moderate malnutrition was present in 12 (32%) children; 25 (68%) were of normal nutritional status. There was no effect of malnutrition on any measure of total drug exposure or on the unbound fraction of nevirapine. Nevirapine exposure was strongly related to dose administered (P = 0.039) and to age (for every yearly increase in age there was an approximately 88% increase in the odds of achieving a therapeutic nevirapine concentration; P = 0.056, 95% confidence interval 0.983-3.585). CONCLUSIONS: Use of divided adult Triomune 30 tablets in treating young children results in significant underdosing. No independent effect of malnutrition on total and unbound nevirapine exposures was observed. These data support the use of bespoke paediatric antiretroviral formulations.